2015
DOI: 10.1186/s12875-015-0289-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving treatment adherence for blood pressure lowering via mobile phone SMS-messages in South Africa: a qualitative evaluation of the SMS-text Adherence SuppoRt (StAR) trial

Abstract: BackgroundEffective use of proven treatments for high blood pressure, a preventable health risk, is challenging for many patients. Prompts via mobile phone SMS-text messaging may improve adherence to clinic visits and treatment, though more research is needed on impact and patient perceptions of such support interventions, especially in low-resource settings.MethodAn individually-randomised controlled trial in a primary care clinic in Cape Town (2012–14), tested the effect of an adherence support intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(144 citation statements)
references
References 25 publications
(25 reference statements)
10
128
2
2
Order By: Relevance
“…This finding concurs with the finding of a recent study in Canada but is in sharp contrast with those of a recent South African study where most participants regarded receiving health messages via cell phones (SMS-text messages) quite acceptable, with some even crediting these messages for their adherence (Afshar et al, 2012;Leon, Surender, Bobrow, Muller, & Farmer, 2015).…”
Section: Discussioncontrasting
confidence: 57%
“…This finding concurs with the finding of a recent study in Canada but is in sharp contrast with those of a recent South African study where most participants regarded receiving health messages via cell phones (SMS-text messages) quite acceptable, with some even crediting these messages for their adherence (Afshar et al, 2012;Leon, Surender, Bobrow, Muller, & Farmer, 2015).…”
Section: Discussioncontrasting
confidence: 57%
“…During our search, we found only one qualitative research study evaluating a text messaging support system for improving adherence for blood pressure lowering in South Africa. 53 …”
Section: Discussionmentioning
confidence: 99%
“…Clinics can use mobile devices to send adherence promoting reminders to diabetics. Research by Leon et al (2015) indicated that adherence support by SMS messages benefitted patients, particularly those who experienced life stressors and those who struggled with adherence.…”
Section: Resultsmentioning
confidence: 99%